How should health leaders approach morally contentious policy issues?. Issue 1 (January 2018) - Kekewich, Michael; Landry, Joshua; Roth, Virginia
In terms of their expertise, experience, and impact on patient care, health leaders occupy an important position in our health system. These leaders are expected to provide value to their constituents, and this value is connected to moral objectives that are fundamental to the delivery of healthcare. In some cases, leaders may interpret a certain politico-medical decision, policy, or directive to interfere with these moral objectives. In these instances, leaders can either expressly object to a decision or sideline moral views while enacting these policies or directives. We present several contemporary examples of these issues as well as the experiences of health leaders. Subsequently, we review relevant sections of the Canadian College of Health Leaders' Code of Ethics to identify existing guidance. Ultimately, we conclude that more work is needed to define the role of leaders in these circumstances, as well as the limitations of any resistance.